PROPOSISI SPIRITUALITAS DALAM REGULASI DIRI BELAJAR SEBAGAI KOPING STRES DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Syahidah Rena (Qiro'ah : Jurnal Pendidikan Agama Islam, 2024)
The ability to know oneself can lead individuals to their goals. On the other hand, self-disregulation will cause emotional and behavioral shocks. To avoid these two forms of interference, the two terms behavioral self-regulation and emotional self-regulation are known. Meanwhile, in correlation to the study of stress coping strategies, these two terms are called "emotion-focused coping and problem-focused coping". This paper aims to discuss forms of learning self-regulation as a form of stress coping based on integrative studies from Western and Islamic perspectives. This research uses a qualitative literature approach which is based on a number of reviews of sources such as books, journals and other research results related to the focus of the researcher's study. This study reveals that the connection between spirituality and self-regulation is connected due to the goal accomplishment factor, when someone with strong faith has a clear and planned effort to achieve their goal compared to groups who have less faith.